Identifying Pure Idioms and Semi-literal Idioms Used in George R. R. Martin’s “Fire and Blood” Chapters 1 and 2 Based on Chitra Fernando’s Theory of Idiomaticity - Nuna, Elma Nailul; Melani, Boniesta Zulandha; Udin, Udin; Junaidi, Ahmad (Journal of Authentic Research, 2025)
This study investigates the use of idiomatic expressions in George R. R. Martin’s Fire and Blood, focusing specifically on Chapters 1 and 2, by identifying and classifying idioms based on Chitra Fernando’s (1996) theory of idiomaticity. The research aims to determine the types and frequency of pure idioms and semi-literal idioms used in the narrative, and to explore their contextual meanings and narrative functions. Employing a mixed-methods approach, the researcher extracted idioms through manual reading and digital tools, then categorized and analyzed them qualitatively. The findings reveal a total of 44 idiomatic expressions, with semi-literal idioms comprising the majority (79.55%) and pure idioms accounting for 20.45%. The dominance of semi-literal idioms suggests a stylistic preference in Martin’s writing for expressions that balance figurative richness with interpretative accessibility. This study affirms the applicability of Fernando’s theory to literary texts, particularly in the fantasy genre, where idioms play a key role in world-building, character development, and thematic resonance. The results contribute to a broader understanding of idiomatic usage in literature and offer practical insights for learners, educators, and future researchers interested in figurative language analysis.